CASH WAQF IN ECONOMIC DEVELOPMENT ISLAMIC ECONOMIC PERSPECTIVE (LITERATURE REVIEW) - Melinda, Eka (Wasīlah: Journal Of Sharia Sciences, 2026)
This article discusses the potential of cash waqf in economic development and cash waqf from an Islamic economic perspective. This research is a qualitative study using a literature study approach, and data is obtained from literature that serves as a reference for the researcher. Society certainly desires a prosperous life, meaning a life of sufficiency, such as sufficient clothing, food, shelter, health, and education. The welfare of the people of a region or country can be pursued through economic development. Economic development can increase per capita income, because economic development is closely related to poverty. Material needs in achieving community welfare can be met through Islamic philanthropy (zakat, waqf, and infaq). The waqf sector in Indonesia has experienced extraordinary growth, and if waqf is managed and empowered productively and professionally by the government and society, it can contribute to the economic development of the community. The potential of waqf is enormous for economic growth because waqf, as a fiscal instrument other than zakat, can be an alternative in addressing social problems such as social inequality and poverty. This research is expected to provide broader knowledge and insight for individual institutions regarding the importance of understanding and the potential of cash waqf in the economic development of the community and can be a contribution of thought for readers and additional references for further researchers.